(untitled) (Computer systems and information technologies, 2022)
Taking into account the conditions of the functioning of modern business, it is necessary to take into account the constant changes that occur in the process of developing projects in IT companies. Therefore, when creating projects, there is a need for a well-founded choice of project management methodologies, which will allow to quickly solve problems that arise in the process of their creation and will provide an opportunity to ensure high efficiency of project-oriented activities of companies. The conducted analysis of the methodologies showed that today there are a sufficient number of them, among which there are rigid and flexible ones. Among the hard methodologies, as Waterfall model, V-model, Incremental model, Spiral model, and Iterative model are known. Among flexible methodologies, the Agile model, as well as Scrum and Kanban are most often used. The following flexible methodologies are also known: Lean, eXtreme Programming (XP), Rational Unified Process (RUP), Dynamic Systems Development Model (DSDM), Rapid Application Development (RAD), and Extreme Programming (XP). It has been determined that most researchers prove in their studies that agile methodologies are more widespread nowadays and are better adapted to the conditions of rapid changes in projects. The only exceptions are those methodologies that apply to certain industries, such as medical, aviation, and others. Such fields involve the use of only brutal methodologies. The article examines the modern Agile approach to project management, its difference from the traditional approach of the rigid Waterfall methodology or others; the scope of application of Agile; a short story; the advantages and disadvantages of implementation and its use. The article provides a comparative analysis of the most popular today’s flexible Scrum and Kanban methodologies. The roles that are indicated in projects in Scrum and Kanban are considered. The events performed by the teams are also analyzed in more detail. The article elaborates a block diagram for a justified choice of Scrum or Kanban methodology. The article is based on research on the international and Ukrainian markets of IT companies. The direction of future research of the authors is to conduct a more detailed analysis and comparison of rigid and flexible methodologies with the aim of using combined forms of project management.